A Dictionary for the Modern Clarinetist - Ellsworth, Jane (Rowman & Littlefield Publishers, 2014)
Titles in Dictionaries for the Modern Musician series offer both the novice and the advanced artist key information designed to convey the field of study and performance for a major instrument or instrument class, as well as the workings of musicians in areas from conducting to composing. Unlike other encyclopedic works, contributions to this series focus primarily on the knowledge required by the contemporary musical student or performer. Each dictionary covers topics from instrument parts to playing technique and major works to key figures. A must-have for any musician’s personal library! The clarinet has played an important role in all kinds of music, ranging from classical to jazz to the traditional music of varying ethnicities and traditions. A beloved band instrument to thousands of school children, the clarinet is also capable of capturing some of the most sublime musical moments in the hands of professional artists. It has found a home in any number of venues, from the great symphonic concert halls to local jazz clubs, from the streets of New Orleans to the film studios of Hollywood. In A Dictionary for the Modern Clarinet, scholar and musician Jane Ellsworth offers lovers of the clarinet the premiere reference book for information about this remarkable instrument. Containing over 400 terms, Ellsworth covers the clarinet's history (including both modern and historical instruments, common and rare), acoustics, construction, fingering systems and mechanisms, and techniques, as well as its more important performers, makers, and scholars. A Dictionary for the Modern Clarinetist will delight clarinet aficionados at all levels. For knowledgeable professionals it will serve as a quick and handy reference guide, useful in the high school or college library and the home teaching studio alike; students and amateurs will find it accessible and full of fascinating information about the world of the clarinet.